APPLICATION OF MEDICAL INFORMATION SYSTEMS IN EDUCATION AND RESEARCH IN MEDICINE - Duisebekova K.S.; Amantay A.A. (Academic Journal of Physical and Chemical Sciences, 2020)
Medical information systems (MIS) - in a broad sense, it is a form of organization in medicine, uniting in the process of activities of physicians, mathematicians, technicians with a complex of technical means and providing the collection, storage, processing, analysis and delivery of medical information of various profiles in the process of solving problems, and in the narrow sense - a complex of mathematical and technical means to ensure the collection, storage, processing and issuance of medical information in solving problems of clinical medicine or health. The general commands for planning and implementing a medical information system are very large and rich. There are necessary requirements for personnel, capital, and the organization itself. Strict requirements for high reliability and user utility for a real-time system significantly increase hardware and software requirements. The scale of the information system requires careful time planning and modular implementation.